New subclass of multivalent functions - Firas Ghanim,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2010)
In this paper we introduce a new subclass M * (α,β,γ,A,λ,ρ)consisting of analytic and multivalent functions with negative coefficients. The object of the paper is to show some properties for the subclass M * (α,β,γ,A,λ,ρ)